A preliminary study on the new geotechnical weathering index in the evaluation of altered biotite granite - Hyun Choi, Seung; Whan Oh, Chang; Ha Lee, Khil; Boo Lee, Young; Kyeong Choi, Eun; Wook Kim, Sung (International Journal of Engineering and Technology, 2018)
The existing chemical index of alteration has a difficulty to evaluate the degree of weathering in biotite granites due to an assumption that K2O content decreases along with Na2O, CaO, and MgO. We found that relative K2O content increases during weathering of biotite granite, as it is retained within such rocks due to (1) the chemical and physical stability of K-feldspar and (2) the formation of illite via incorporation of K ions released from biotite. The calculated ranges of most chemical indexes for biotite granite weathering do not show a good correlation with the weathering grade except the CIW, WIP and V indexes. The range of the CIW, WIP and V indexes according to the weathering grade were very small, and thus small errors in whole-rock chemical analyses can produce large discrepancies in calculated values. Further, the WPI index is a relative weathering index that depends on the composition of a fresh standard sample and cannot be applied to determine the absolute degree of weathering in granites if no protolith is available. We suggest a new weathering index (BWI; Biotite weathering index) based on a decrease in the number of K ions in the interlayer site of biotite during weathering of granite. Newly calculated values show a much wider range than the CIW, WIP and V indexes with a good relationship with a weathering grade. Therefore, it is necessary to establish the new index for a detailed classification of weathering degree.Â Â